Development of a Game-Based Science Learning Model Oriented to Papuan Local Culture for Grade IV Elementary School Students - Sirjon; Moch Sukardjo; Etin Solihatin (JTP - Jurnal Teknologi Pendidikan, 2023)
The purpose of this study was to develop a game-based science learning model oriented towards local Papuan culture for fourth grade elementary school students that was appropriate and effective. This study uses a qualitative approach with the R & D (Research and Development) research method which collaborates 3 development models namely the first step of the Borg & Gall model, the Dick & Carey model, and the Lee & Owen model. Data analysis was carried out through formative evaluation and effectiveness testing with the t test. The results of the formative evaluation show that the average feasibility test for material experts, instructional design experts, and media experts is 3.93 with good conclusions, one-to-one evaluation with students obtains an average of 3.05 with good conclusions, the small group evaluation obtains average 3.43 with very good conclusions, and the field trial evaluation obtained an average value of 3.61 with very good conclusions, so it was concluded that the Papuan local culture-oriented game-based science learning model for fourth grade elementary school students was very good. Testing the effectiveness of developing a Papuan local culture-oriented game-based science learning model for grade IV elementary school students was tested through the t-test. The results show the value of Sig. (2-tailed) of 0.000 <0.05, then there is a significant difference between science learning outcomes on the pretest and posttest data, so it can be concluded that the Papuan local culture-oriented game-based science learning model is effective for improving learning outcomes for fourth grade elementary school students.